Plasma-cell-interaction: Expression of surface molecules on HaCaT keratinocytes after treatment with dielectric barrier discharge (DBD) plasma - Haertel, B.; Lindequist, U.; Haehnel, M.; Wende, K.; Oehmigen, K.; von Woedtke, T. (2011 Abstracts IEEE International Conference on Plasma Science, 2011)
Summary form only given. Non-thermal atmospheric-pressure plasmas have been developed that will be used for several indications, e.g. also in medicine. Here, living tissues and cells are in focus of plasma treatment, e.g. to improve wound healing or to induce apoptosis and growth arrest in tumour cells. Detailed investigations of plasma-cell interactions are strongly needed. The cell membrane with its embedded proteins is the first target of plasma treatment. Such cell surface molecules as integrins, cadherins or the epidermal growth factor receptor (EGFR) are of importance in wound healing and also for development of cancer metastasis. This study focused on measurement of cell surface molecules on human HaCaT keratinocytes promoting adhesion, migration and proliferation as one important feature of plasma-cell interactions. HaCaT keratinocytes were treated with plasma by a surface dielectric barrier discharge in air. Cell surface molecules were analyzed by flow cytometry 24h after plasma treatment. Besides a reduction of cell viability a significant down regulation of E-cadherin and the EGFR expression was observed. The influence on α 2 - and β 1 -integrin was less pronounced and expression of ICAM-1 was not affected. The extent of effects depended on the treatment regimen and the exposure time of cells to the plasma. The two-dimensional culture of HaCaT keratinocytes are proved to be a suitable method of investigating plasma-cell interactions.